Osteonecrosis After Contralateral in Situ Prophylactic Pinning for a Slipped Capital Femoral Epiphysis: A Case Report. Issue 3 (July 2018) - Chargui, Moez; Dhouib, Amira; Esposito, Fabiana; Spyropoulou, Vasiliki; Steiger, Christina; Dayer, Romain; Ceroni, Dimitri
Abstract : Case: We report the case of an 11-year-old girl who developed osteonecrosis of the femoral head in the radiographically normal, asymptomatic left hip that had been fixed prophylactically in the context of a slipped capital femoral epiphysis (SCFE) that had been detected on the contralateral hip. The etiology of the osteonecrosis remains unknown. Conclusion: This case report demonstrates that prophylactic fixation of a radiographically normal, asymptomatic hip in the context of an SCFE on the contralateral side has the potential for substantial complications. Therefore, the risk of osteonecrosis in the prophylactically pinned hip should be carefully considered because this complication may have devastating functional consequences.